Is there a relationship between EEG and sTMS neurophysiological markers of the putative human mirror neuron system?. Issue 12 (7th November 2021) - Bekkali, Soukayna; Youssef, George J.; Donaldson, Peter H.; Hyde, Christian; Do, Michael; He, Jason L.; Barhoun, Pamela; Enticott, Peter G.
Abstract: The mirror neuron system (MNS) has been theorized to play a neurobiological role in a number of social cognitive abilities and is commonly indexed putatively in humans via interpersonal motor resonance (IMR) and mu suppression. Although both indices are thought to measure similar neuronal populations (i.e., "mirror neurons"), it has been suggested that these methods are unrelated, and therefore, incompatible. However, prior studies reporting no relationships were typically conducted in small and underpowered samples. Thus, we aimed to investigate this potential association in a large sample of neurotypical adults ( N  = 116; 72 females). Participants underwent transcranial magnetic stimulation (TMS), electromyography (EMG), and electroencephalography (EEG) during the observation of videos of actors performing grasping actions in order to index IMR and mu suppression (in beta, lower alpha, and upper alpha bandwidths). A series of linear regressions revealed no associations between IMR and each of the mu suppression bandwidths. Supplementary Bayesian analyses provided further evidence in favor of the null (B01  = 8.85–8.93), providing further support for no association between the two indices of MNS activity. Our findings suggest that these two measures may indeed be unrelated indices that perhaps assess different neurophysiological aspects of the MNS. These results have important implications for future studies examining the MNS. Abstract : In a large sample of healthy adults, we assessed whether two predominantly used measures of the human mirror neuron system (MNS) are related. Results revealed strong evidence against an association, indicating that future researchers must carefully select their measures and embrace more versatile multi‐methodological approaches to indexing the MNS.